Modalizadores deônticos de necessidade proposicionais e interacionais em carta política - Fagundes, Nathália Rohde (2025)
This study was conducted on the functioning of deontic necessity modalizers at both the propositional and interactional levels, as observed in the political letter “Garantir o direito à alimentação e combater a fome em tempos de coronavírus: a vida e a dignidade humana em primeiro lugar!” (FBSSAN, 2020), which was produced and published in the first semester of the Covid-19 pandemic. Through a theoretical, qualitative study guided by a descriptive- interpretative analysis, grounded in the principles of Text Linguistics and Functionalist Studies, this research aimed to determine whether differences and/or similarities existed in the functioning of these modalizers in the aforementioned political letter. This study is justified by the scarcity of research on the political letter genre and by the fact that this genre provides a relatively suitable space for the occurrence of different and even conflicting deontic elements. The selection, classification, and analysis of the modalizers are theoretically based primarily on the works of Lyons (1977), Dascal (1986), Neves (1986; 2000; 2006), Koch (2011), Corbari (2008; 2013), and Oliveira (2022). The discussion on the political letter genre follows the perspectives of Sussmann (1959; 1962), Marcuschi (2005; 2008), and Bazerman (2020). The occurrence of deontic modalizers was found to be directly related to “deontic statements”, understood here as textual segments immediately preceding the segments in which the respective modalizers appear, reinforcing the notion of obligation generally conveyed throughout the text. No significant difference was observed in the relationship between the deontic necessity modalizer (whether propositional or interactional) and the preceding deontic statement. Both types of modalizers serve to introduce new recommendations, indicate how a previous recommendation should be followed, or further elaborate on a previous recommendation. The primary distinction lies in the content of the recommendations associated with each type of modalizer. This study contributes to the analysis of deontic necessity modalizers concerning the political letter genre by examining these linguistic elements in a text produced during a politically and socially significant period—the Covid-19 pandemic. Additionally, it advances research on modalization by investigating modalizing elements and their patterns of use concerning the interactional layer and propositional content.